Chrysin Quantification from Leaf Samples of Dolichandrone Falcata - R. P. Bansode,; S. E. Mahamune, (International Journal of Scientific Research in Science and Technology, 2024)
The chrysin quantitative from leaf samples were analysed using HPTLC. All the samples were active on TLC plate and revealed the presence of chrysin. The maximum amount of chrysin was obtained from in vivo leaf powder (0.60 μg) than in vitro leaf powder.
Keywords: Chrysin; Dolichandrone falcata; leaves; HPTLC